HERVs Endophenotype in Autism Spectrum Disorder: Human Endogenous Retroviruses, Specific Immunoreactivity, and Disease Association in Different Family Members - Marco Bo; Alessandra Carta; Chiara Cipriani; Vanna Cavassa; Elena Rita Simula; Nguyen Thi Huyen; Giang Thi Hang Phan; Marta Noli; Claudia Matteucci; Stefano Sotgiu; Emanuela Balestrieri; Leonardo Antonio Sechi (Microorganisms)
Increasing evidence indicates that human endogenous retroviruses (HERVs) are important to human health and are an underexplored component of many diseases. Certain HERV families show unique expression patterns and immune responses in autism spectrum disorder (ASD) patients compared to healthy controls, suggesting their potential as biomarkers. Despite these interesting findings, the role of HERVs in ASD needs to be further investigated. In this review, we discuss recent advances in genetic research on ASD, with a particular emphasis on the implications of HERVs on neurodevelopment and future genomic initiatives aimed at discovering ASD-related genes through Artificial Intelligence. Given their pro-inflammatory and autoimmune characteristics, the existing literature suggests that HERVs may contribute to the onset or worsening of ASD in individuals with a genetic predisposition. Therefore, we propose that investigating their fundamental properties could not only improve existing therapies but also pave the way for new therapeutic strategies.